Deuteronomy's Prodigal Son: Deut. 21:18-21 and the Agenda of the D Source. - Boyd, Samuel L. (Biblical Interpretation, 2020)
This article examines the ways in which the law of the rebellious and stubborn son in Deut. 21:18-21 supports the agenda of the D source to subordinate any basis of authority in ancient Israel to its own legal vision of centralization. In particular, I explore theories regarding the origin of Deut. 21:18-21 as pre-deuteronomic and argue that, whatever its pre-history, the law of the rebellious and stubborn son functions well in the legal and religious rhetoric of D. I further support this analysis of Deut. 21:18-21 by recourse to and comparison with similar family laws in the Covenant Code and Holiness Legislation. Finally, I offer thoughts on the manner in which the severity of Deut. 21:18-21 explains two facets of the reception history of this passage.